Crustal evolution of Western Europe: Constraints from detrital zircon U-Pb-Hf-O isotopes - Avigad, Dov; Abbo, Avishai; Gerdes, Axel; Schmitt, Axel Karl (Gondwana research, 2022)
We studied detrital zircon from black sand of the Rhone River delta (southern France) which drains significant parts of Western Europe. Zircon U-Pb geochronology shows that the black sand is an extraordinary sampler of all major episodes of European magmatism peaking at 0.55 Ga (Cadomian), 0.45 Ga (Cenerian) and 0.31 Ga (Variscan). Hf in detrital zircon suggest that European magmatic episodes involved continuous crustal reworking along a crustal evolutionary array with Hf-TDM ages pointing to the reworking of an older, Mesoproterozoic (1.0-1.5 Ga) crustal reservoir. However, the coupling of O isotopes shows that the majority of the zircon possess elevated δ18O values indicating the involvement of a noteworthy sedimentary component in the genesis of European granitoids. Therefore, a preponderance of the obtained Hf-TDM ages are mixed and do not designate the reworking of Mesoproterozoic crust. The Variscan and post-Variscan intervals include also a significant proportion of detrital zircon with mantle-like δ18O (≤6.5 ‰) while retaining Mesoproterozoic Hf model ages. Zircon of this type are uncommon in European granitoids and their origin in Rhone delta is therefore not clear, but we tend to interpret the contrasting isotopic signatures as indicating crystallization from juvenile melts whose Hf reflects source contamination. Few ancient, pre-Neoproterozoic continental slivers are scattered in Western Europe, yet our U-Pb-Hf-O detrital zircon data do not support the widespread reworking of a pre-Neoproterozoic deep crustal reservoir in this region. The prevalent oldest rocks of Western Europe are Late Ediacaran Cadomian clastic sediments, mostly derived from the erosion of Gondwana Pan-African orogens with variable contributions from proximal Cadomian arcs. The apparent Mesoproterozoic Nd and Hf model ages of many European granitoids are likely inherited from the isotopic properties of their Late Ediacaran (and younger) precursor sediments which carry the isotopic composition of the North Gondwana crust.